2012
DOI: 10.1143/jpsjs.81sb.sb068
|View full text |Cite
|
Sign up to set email alerts
|

Development of Point-Contact Spectroscopy of Heavy-Fermion Superconductors under Pressure

Abstract: We have developed a new method to perform point-contact spectroscopy PCS under pressure, in which a thin-film deposition technique is used for making a point contact. We investigated a pressure dependence of the point-contact spectra of the heavy-fermion superconductor URu 2 Si 2 single crystal. In PCS of URu 2 Si 2 , two characteristic components evolve at low temperatures: one is a symmetric structure with respect to zero bias voltage suggesting a gap of the density of states at the Fermi surface, and the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This method has been successfully implemented for the study of the superconducting order parameter of various superconductors at ambient pressure (see the review Ref. 38 and references within), as well as the hidden order and antiferromagnetic phases of URu 2 Si 2 at high pressure, 58,59 with the advantage of reliable stability over a large temperature range.…”
Section: Soft Pcs Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method has been successfully implemented for the study of the superconducting order parameter of various superconductors at ambient pressure (see the review Ref. 38 and references within), as well as the hidden order and antiferromagnetic phases of URu 2 Si 2 at high pressure, 58,59 with the advantage of reliable stability over a large temperature range.…”
Section: Soft Pcs Measurementsmentioning
confidence: 99%
“…In recent years it has been demonstrated that the soft point-contact spectroscopy can be adapted to a highpressure environment. 58,59 Instead of the conventional PCS method with a sharp metal tip, SPCS contacts used here are made by dipping the end of a 25 µm-diameter platinum wire into Ag epoxy and attaching it to the [001] surface of the crystal. This method has been successfully implemented for the study of the superconducting order parameter of various superconductors at ambient pressure (see the review Ref.…”
Section: Soft Pcs Measurementsmentioning
confidence: 99%
“…We have developed a new method of making a PC to be able to measure PC spectrum under pressure and high magnetic field [19]. In our method of making a PC, an epoxide-based adhesive was used as an insulation material, and a silver layer was deposited by a vacuum evaporation equipment to serve as a counter electrode.…”
Section: Experimental Methodsmentioning
confidence: 99%